Application of the Problem Based Learning Model Through the Use of Waste as a Teaching Aid Media in Elementary School Students - Iswan, Iswan; Habillah, Refiana (Journal of Education and Training, 2024)
Research with the title Application of the Problem Based Learning Model through the Use of Waste as a Teaching Aid Media for Elementary School Students. This research is motivated by the importance of using waste as a teaching aid medium in the learning process for elementary school students, which needs to be given a very interesting priority, given its existence. Efforts to utilize waste so that used items that are no longer used can be processed as media materials for teaching aids to support the learning process. The research method used was an experimental method, the population used was students from the Mazroatul Ulum Private Madrasah Ibtidaiyyah, South Tangerang. Indonesia, the number of samples in the research was 30 students. The data collection technique uses questionnaires, pretest posttest and documentation. The research results show that the R value or correlation coefficient between the Problem Based Learning variable on waste utilization is 0.982, meaning the program has an influence, namely 0.982, which means sufficient or moderate. This can be seen from: 0.00-0.20 means very low or very weak, 0.20-0.40 means low or weak but certain, 0.40-0.70 means quite means moderate, 0.70- 0.90 means high or strong, 0.90-1.00 means very high or very strong. Meanwhile, Rsquare is also called the coefficient of determination. It can be read that the Rsquare value shows 0.633. This figure can be interpreted that the school environment on achievement motivation is 63.3% while the remaining 76.7% is influenced by other factors.